Apakah Indeks Saham Syariah Indonesia (ISSO) Memediasi Pengaruh Nilai Tukar Terhadap Return Saham Syariah ? - Sri Hermuningsih; Hanita Yuniati; Mujino Mujino (Jurnal Manajemen dan Bisnis Indonesia, 2017)
This study aims to analyze the effect of Exchange Rate on Stock Return with Sharia Stock Index as Mediation. The population in this study is the sharia shares listing on the Indonesia Stock Exchange. Sampling using purposive sampling method, with criteria List of sharia firms in the Property and Real Estate sectors which are categorized as Sharia (ISSI) Index which is constant (fixed) during December 2015-May 2016 period. Data analysis using regression analysis. The result of the research shows that the exchange rate has an effect on the Return of Sharia Shares and Sharia Stock Index of Indonesia influential on Sharia Return Shares. Indonesia Sharia Stock Index is able to mediate between Exchange Rate and Sharia Return Shares Keywords : Nilai Tukar, Indeks Saham Syariah Indonesia, Return Saham Syariah.